Evolutionary Physiology and Biochemistry - Advances and Perspectives 2018
DOI: 10.5772/intechopen.73662
|View full text |Cite
|
Sign up to set email alerts
|

Systems Evolutionary Biology of Waddington’s Canalization and Genetic Assimilation

Abstract: In recent years, there has been growing interest in computer modeling of the evolution of gene and cell regulatory networks, in general, and in computational studies of the classic ideas of Baldwin, Schmalhausen, Waddington, and followers, in particular. Two related aspects of Waddington's evolutionary theories are the concepts of canalization and of genetic assimilation. Canalization is associated with the robust development of an individual to diverse perturbations and noise, though, when fluctuations in dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 131 publications
(203 reference statements)
0
1
0
Order By: Relevance
“…The study showed that deletions do not affect the asymmetry of the Drosophila wing, but the development of canalization in a period of time changes. Consequently, genetic deletions have an impact on the canalization of the development of traits, but not on the stability of the development [34,35]. Genetic assimilation is the subsequent genetic fixing of the new trait in the population.…”
Section: Epigenetics As a New Branch Of Genetics 31 Interspecific DImentioning
confidence: 99%
“…The study showed that deletions do not affect the asymmetry of the Drosophila wing, but the development of canalization in a period of time changes. Consequently, genetic deletions have an impact on the canalization of the development of traits, but not on the stability of the development [34,35]. Genetic assimilation is the subsequent genetic fixing of the new trait in the population.…”
Section: Epigenetics As a New Branch Of Genetics 31 Interspecific DImentioning
confidence: 99%